THE COMPOSITION OF GOVERNMENT EXPENDITURE AND ECONOMIC GROWTH - Všetičková, Simona; Potužák, Pavel; Slaný, Martin, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2015)
This thesis examines the effect of the government expenditure structure on the economic growth. The objective is to determine which components of public expenditures are growth enhancing and which growth retarding. The theoretical model is set into the endogenous growth framework and describes the growth mechanism of productive and unproductive government expenditures. The growth impact of public spending composition is analysed for 18 European countries from 1996 to 2012. The empirical part is based on the panel data analysis. The empirical findings suggest that reallocating public resources towards education and health can promote growth. Whereas, higher expenditures on spending and defence are likely to be growth-retarding.
Vedoucí práce: Pavel Potužák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses